The Basic Colors in The Structure of Kurdish and English Idioms - Galawezh Othman Qadr; Prof. Dr. Rafiq Muhammad shwani (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
This study compares the structure of color-related idiomatic expressions in the Kurdish and English languages. It concentrates on the hidden aspects of meanings and lexical similarities and differences that exist in both languages. Because idiom as a syntactical form and a lexical unit is a peculiar structure of any language. Idioms have established meaning that cannot have a literal translation, reflecting the culture of an area; they have multi-meanings with a fixed form. The colors have significant participation in idiom’s structures, particularly the basic colors (red, yellow, and blue), which are the items of this study, because color is an absolute visible object. It is one of the essential components of nature. It has its impact on the entire common ideology of any era. Also, color is a science that explains color’s relations and the human psychological state. Hence, the rate of color participation in Kurdish and English languages’ idioms that covey the same sense or a different one, the present study draws an intertwined picture of Kurdish and English cultures, it shows the human’s experiments in two distinct nations. Colors in Kurdish idioms give substantial meaning to the idioms. Idioms have the connotation of serious terrible, happiness, sadness, pride, humiliation, distress, amenity, oppressor, oppressed, persecution, and persecutor. The color idioms have an expanded meaning, so having at least a color word or an expression that expresses color. It has inexplicit meaning, or it can be used indirectly. Comparing the basic colors in both languages with different cultures, the color idioms are very rich in having similar examples but with conveying different meanings. This is a gate to English language learners in order to be familiar with hidden and complicated aspects of the language. The content of the research consists of two parts: the first part; idiom’s concept, idiom’s characteristics, color, and its history, and the basic colors in the Kurdish language.